Epigenetic silencing of chemokine CCL2 represses macrophage infiltration to potentiate tumor development in small cell lung cancer. (28th February 2021) - Zheng, Yang; Wang, Zhihong; Wei, Simeng; Liu, Ziling; Chen, Guojiang
Abstract: Highly invasive and rapidly fatal, small-cell lung cancer (SCLC) has been an insurmountable gulf since discovery. Innate immunity plays a vital role in anti-tumor response, among which macrophages contribute to an indispensable character. Here, we found that macrophage infiltration in SCLC reduced significantly in a stage-dependent manner, attributed to the decreased expression of CCL2, a potent chemoattractant for monocytes. Validated by ChIP-qPCR and MassArray methylation analysis, CCL2 expression was inhibited by EZH2-mediated H3K27me3 in the enhancer regions and DNMT1-mediated DNA methylation in the promoter regions, the process of which could be reversed by small-molecular compounds, EPZ011989 and Decitabine. Direct cell-cell contact between SCLC cells and macrophages skewed the phenotype of macrophages to be more M1-like. Furthermore, in an ectopic engraft model of SCLC, disruption of EZH2/DNMT1 function using the combination treatment of EPZ011989 and Decitabine potently abrogated the inhibition of macrophage infiltration and thus suppressed tumor growth, the effect of which was impaired by CCL2 neutralization or macrophage depletion. Overall, this work provides new insights into the role of macrophages in SCLC and establishes a rationale for constructing novel therapeutic avenues for SCLC patients. Highlights: Decreased expression of CCL2 led to low macrophage infiltration in SCLC. Inbition of CCL2 by DNMT1 and EZH2/H3K27me3 could be reversed by EPZ and DAC. Combination treatment of EPZ and DAC reduced mice tumor burden of SCLC. Increased M1-type macrophages exihibited anti-tumor effects in SCLC.